PEMBERDAYAAN MASYARAKAT DALAM MENGATASI PENURUNAN JUMLAH PERAJIN DI KAMPUNG BATIK REJOMULYO KOTA SEMARANG - Afiska Nafisatun Qori’ah; Retna Hanani (Journal of Management and Public Policy, 2026)
The batik industry is part of Indonesia's cultural heritage, possessing economic and social value for the community. However, the Rejomulyo Batik Village in Semarang City faces a year-over year decline in the number of artisans, threatening the sustainability of the local batik business. This situation highlights the importance of community empowerment involving collaborative efforts between the government and artisan communities. This study aims to analyze empowerment of the batik artisan in the Rejomulyo Batik Village in Semarang and to identify supporting and inhibiting factors. Informants were selected using purposive sampling. The results indicate that empowerment is carried out through batik training, production facilitation, business mentoring, and promotional support. This empowerment contributes to improving artisan skills and strengthening the existence of the Rejomulyo Batik Village as a batik center. However, these efforts have not been fully able to prevent the decline in artisan numbers. Supporting factors include training programs and the potential of Semarang's distinctive batik, while inhibiting factors include budget constraints and weak coordination between the actors involved.